Using artificially generated pictures in customer-facing systems: an evaluation study with data-driven personas. Issue 5 (4th April 2022) - Salminen, Joni; Jung, Soon-gyo; Kamel, Ahmed Mohamed Sayed; Santos, João M.; Jansen, Bernard J.
ABSTRACT: We conduct two studies to evaluate the suitability of artificially generated facial pictures for use in a customer-facing system using data-driven personas. STUDY 1 investigates the quality of a sample of 1, 000 artificially generated facial pictures. Obtaining 6, 812 crowd judgments, we find that 90% of the images are rated medium quality or better. STUDY 2 examines the application of artificially generated facial pictures in data-driven personas using an experimental setting where the high-quality pictures are implemented in persona profiles. Based on 496 participants using 4 persona treatments (2 × 2 research design), findings of Bayesian analysis show that using the artificial pictures in persona profiles did not decrease the scores for Authenticity, Clarity, Empathy, and Willingness to Use of the data-driven personas.